First Record for the Histioteuthis reversa (Verrill, 1880), (Cephalopoda/Histioteuthidae) in the Gulf of Antalya/ Turkey - USTUNER, Hatice; GOKOGLU, Mehmet (Acta Aquatica: Aquatic Sciences Journal, 2022)
A different squid species was caught with a trawling net at the coordinates of 36o 39'.431'' N; 31o 9.841''E and a depth of approximately 600-650 m in the Gulf of Antalya. In the identification of species, this squid species was determined to be Histioteuthis reversa (Verrill, 1880). This is the second record for the squid species in the Mediterranean Coast of Turkey and the first record in the Gulf of Antalya.Keywords: Gulf of Antalya; Histioteuthis reversa; Mediterranean; Record